The impacts of the Henry Review recommendations on the private rental market: Savings income discount and rent assistance - Wood, G.; Ong, Rachel; McMurray, Clinton (AHURI Ltd, 2011)
This is the first of two Final Reports that aims to address the following research question highlighted in AHURI’s housing supply research brief: What is the impact on supply and affordability from implementation of the Henry Review recommendations in relation to negative gearing, land tax and stamp duty?